PERMAINAN FLASHCARD BERPENGARUH TERHADAP PERILAKU HIPERAKTIF PADA ANAK TUNAGRAHITA DI SLB ASY SYAFI’IYAH CILANGKAP - Achwan Achwan; Andy Martahan Andreas H; Mila Amaliya; durratul Jihan H; Angela Saurulita S; Cintia Indah Triyanto P; Nilzam Nasyid Robbani (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2023)
Hyperactive behavior is one of the behavioral deviations that can be reduced with a social approach, one of which is through games. One game that can be used to reduce this behavior is a flashcard game as a means of channeling pent-up emotional energy caused by environmental restrictions on behavior. Purpose this community service to determine the effect of flashcard games on the hyperactive behavior of mentally retarded children. This community service was carried out at SD Tunagrahita SLB Asy-Syafi'iyah for grade 1 students in February - March 2023. There were 6 participants in this community service. Evaluation was carried out before and after the intervention by means of interviews using the ACTRS form. Participants were selected based on the criteria for experiencing hyperactivity aged 6-8 years in good health and permitted by their parents. The intervention was given 5 meetings with an intensity of once a week for 60 minutes. There was a change in 1 child, during 5 meetings, it showed that providing flashcard games had an effect on reducing hyperactive behavior. Conclusion: Flashcard games had an effect on the hyperactive behavior of mentally retarded children in grade 1 elementary school for the mentally retarded SLB Asy-Syafi'iyah in 2023. Conclusion: Flashcard games have little effect on the hyperactive behavior of mentally retarded children in mentally retarded elementary school class 1 SLB Asy-Syafi'iyah in 2023.